Dual Circularly Polarized Bow-Tie-Shaped Stacked Yagi-Uda Antenna Arrays for Internet of Things Applications - Tae-Hyeon Kim; Mohamed Elhefnawy; Kyoung-Hun Kim; Wang-Sang Lee (IEEE Access)
This paper presents the design and analysis of two dual circularly polarized stacked Yagi-Uda antenna arrays, referred to as Type A and Type B. The proposed Type A Yagi-Uda antenna array consists of four printed bow-tie-shaped elements arranged at different angles: a director, a reflector, and two orthogonal driven elements. The driven elements are connected to coaxial cables via LC baluns. The Type B configuration introduces a complementary slotted bow-tie director element in place of the printed one, while the driven and reflector elements remain unchanged. Exciting the upper driven element generates right-hand circular polarization (RHCP), whereas left-hand circular polarization (LHCP) is achieved when the lower driven element is excited. Both proposed antenna arrays share the same dimensions of $0.39λ _{0} × 0.39λ _{0} × 0.27λ _{0}$ , where $λ _{0}$ represents the free-space wavelength at the operating frequency of 2.45 GHz. Measured results confirm that Type B outperforms Type A in several aspects. The Type B antenna array achieves a fractional impedance bandwidth of 8%, a 3-dB axial ratio (AR) bandwidth of 19.6%, and a peak gain of 4.49 dBic. In comparison, Type A exhibits a fractional impedance bandwidth of 2.45%, a 3-dB axial ratio bandwidth of 2.45%, and a peak gain of 3.5 dBic. These findings highlight the effectiveness of the complementary slotted bow-tie director in enhancing antenna performance, making Type B a promising candidate for Internet of Things (IoT) applications.